Correlation Between Rift Valley Fever Virus (RVFV) Neutralizing Antibody Titers in Vaccinated Sheep and Effective Dose 50 (ED50) in Vaccinated Mice - Khafagi, Heba A; Aziz, Heba MG Abdel; AM, Amal; WM, Barghooth; Sharfik, Narmeen G (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Rift valley fever is an arthropod-born, multispecies zoonotic viral disease. Control of RVF disease depends mainly on vector control and vaccination of susceptible animals. The present work aims to detect the correlation between Rift Valley Fever Virus (RVFV) neutralizing antibody titers in vaccinated sheep using Serum Neutralization test as in vitro test and effective dose fifty in vaccinated mice as in vivo potency test and determine if they can be alternative to each other. In this work,17 inactivated RVFV vaccine batches were evaluated, applying SNT for serum samples of vaccinated sheep and ED50 in vaccinated mice. The two models of tests showed compatible results, where the same 14 vaccine batches showed satisfactory results [(SNT >1.5) and (ED50 <0.02)], while the other three batches revealed unsatisfactory results in both two tests. Statistical analysis of results using Wilcoxon’s test was (0.0001), indicating a significant correlation between the testsso it could be recommended to depend on SNT instead of mice inoculation in the evaluation of RVF vaccine to reduce the numbers of animals being used and to avoid the possible public health hazard.